AKIBAT HUKUM DARI PERKAWINAN DENGAN PENGGUNAAN DATA PALSU DI KOTA PEKANBARU - Firdaus, Annisa; Deliana, Evi; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a family happy and eternal based on god. Marriage is legal if it is carried out according to the respective laws and beliefs and is recorded according to the applicable laws and regulations as required in Article 2 paragraph (1) and (2) Law Number 1 of 1974. Against a legal marriage has legal consequences on the husband, wife and children relating to the position of the husband, wife and assets as well as the position of the child, parents and guardianship. Seeing the clarity of the provisions regarding the legal conditions of marriage, in the field there are still irregularities regarding the implementation of the marriage, one example is falsification of data. Crimes concerning falsification or abbreviated as falsification crimes are crimes in which there is an element of an untrue or false state of something (object) which appears from the outside as if it is true even though it actually contradicts the truth.This type of research is sociological, because in this study the author directly conducts research at the location or place under study in order to provide a clear picture of the problem under study. This research was conducted at the Pekanbaru Religious Court, and the Office of Religious Affairs, Kec. Pekanbaru City and the Office of Religious Affairs, Kec. Marpoyan Damai, while the population and sample are cases of marriage annulment caused by the use of false data. The data sources used, primary data, secondary data and tertiary data, data collection techniques in this study with interviews and literature study.From the research results, there are two main points that can be concluded. First, the legal consequences arising from a marriage with false data in the city of Pekanbaru is terminating the marriage by means of a marriage cancellation, so that the legal consequences arising from the marriage are the same as other marriage cancellations written in the Marriage Law Number 1 of 1974 and also Compilation Islamic law. The legal consequences that arise include the relationship between husband and wife, children born from the marriage and also third parties. Second, the legal protection given to a wife who is married to a partner who uses fake data is preventive legal protection and repressive legal protection.Keywords : Because of law – Marrige - Fake data